Effects of different processing parameters on the semisolid microstructure of Al6061 produced by a direct thermal method - M. F. M., Tajudin; Asnul Hadi, Ahmad; Mohd Rashidi, Maarof (IOP Publishing Ltd, 2021)
The effect of different processing parameters consist of pouring temperature and holding time on the semisolid microstructure of Al6061 feedstock billet produced by direct thermal method has been investigated in the present paper. In this experimental works, molten aluminium alloy 6061 was poured into a thin cylindrical copper mould at a constant temperature of 660 °C and held at different holding times of 20 s, 40 s, and 60 s. After it reached the desired holding time, the copper mould was then quenched into room temperature water. The microstructure formation of feedstock billets was characterized after the feedstock billets were taken out from the mould. Results show that, due to the rapid cooling condition of the molten 6061 inside the copper mould, more globular microstructures were obtained. The sample produced with a pouring temperature of 660 °C and holding time of 20 s, globular microstructure were apparent. Simultaneously, the sample with a pouring temperature of 660 °C and a holding time of 20 s produced smaller grain size than the sample with a pouring temperature of 660 °C and a holding time of 40 s and 60 s. Based on the results, the globular microstructures were superior at a shorter holding time, which allowed them to be quenched faster into room temperature water. The results from this experimental works suggest that the DTM feedstock billet globular microstructure formation merely depended on the heat convection of the molten alloy out from the copper mould. The faster heat convection out from the molten alloy which retarded the formation of dendritic microstructure thus transformed it into a globular microstructure for semisolid metal processing